A family case report of parathyroid carcinoma associated with CDC73 mutation in hyperparathyroidism-jaw tumor syndrome - Gu, Yian; Ye, Yuanyuan; Shu, Hua; Chang, Lina; Xie, Yinghui; Li, Fengao; Zhu, Tiehong; Liu, Ming; He, Qing (Frontiers in Endocrinology, 2024)
Background: Hereditary primary hyperparathyroidism (PHPT) accounts for 5-10% of all PHPT cases, necessitating genetic testing for diagnosis and management. Among these, hyperparathyroidism-jaw tumor syndrome (HPT-JT) is an autosomal dominant disorder caused by CDC73 mutations with variable clinical presentations and incomplete symptoms.The proband, diagnosed with PHPT, underwent parathyroidectomy at the age of 41 with pathological examination of parathyroid carcinoma (PC).Hereditary PHPT was initially suspected due to the early-onset PHPT and family history. Genetic testing identified a heterozygous CDC73 mutation, NM_024529.4: c. 687_688delAG (p. Arg229Serfs*37). Even in the absence of jaw tumors, the diagnosis of HPT-JT was confirmed based on the discovery of renal cysts. A secondary thyroidectomy was performed to reduce the risk of recurrence.Genetic testing is strongly recommended in cases of early-onset PHPT, family history, jaw tumors, renal and uterine involvement, atypical parathyroid tumors, and PC. This testing provides valuable information for personalized management, and counseling is available for affected families.